The experience of ICU nurses in caring for Covid-19 patients from the perspective of physical well-being and coping strategies - Ab Razak, Liyana Syatirah; Mohamed Ludin, Salizar (2023)
The covid-19 pandemic caused the infected patients' condition to deteriorate and need to be admitted to the ICU, thus, this impact on the nurses' physical well-being. Majority of the nurses were having headaches, insomnia, hot and sweat a lot, anoxia, chest pain, and fatigue due to long duration of wearing PPE. The study aims to explore how the Covid-19 pandemic has impacted the nurses' physical well-being and the coping mechanism they used to overcome the hurdle and problems.